Pemberdayaan Kemampuan Menulis dalam Bahasa Inggris pada siswa SMP melalui Recount Text Writing - Rindang Widiningrum; Suzana Maria Luki Astuti Fajarini; Erio FanggidaE; Deta Maria Sri Darta (Magistrorum et Scholarium: Jurnal Pengabdian Masyarakat, 2022)
Literacy is not as simple as “ability to read and write”. Students deal a lot with reading, but they still have problems delivering their ideas in writing. This community service aims to assist students of SMP Pangudi Luhur Salatiga to write their experience they had in the form of recount text. The activity is scheduled when students are having their school break for a week. Instructions, guidelines, consultation, and accompaniment were provided to augment students’ first drafts. The result of this activity reveals that although it is considered difficult, writing is enjoyable. Students’ productivity shows their enthusiasm and eagerness to write about their past experiences. An anthology of recount texts is the final result of their work.